STUDY OF THE STABILITY CONDITIONS OF A HIGH CUT SLOPE ALONG EGNATIA HIGHWAY (ASPROVALTA - MACEDONIA) - Στιμάρατζης Θ.; Χρηστάρας Β.; Δημόπουλος Γ.; Κίλιας A.; Χατζηαγγέλου M.; Χατζήγώγος Ν. (Bulletin of the Geological Society of Greece, 2004)
This study is about the stability conditions of a high cut slope as well as the possible measures of restoration, along the Egnatia Highway (deviation of Asprovalta). The study includes: the topographic map of the landslide and the 3-D view with the use of Geographical Information Systems, the analysis of geological and petrologie data from the samples of five core drillings, the soil mechanics laboratory tests, the determination of the causes and the landslide mechanisms and finally the slope stability analysis with «classic» methods such as Bishop, Janbu, Morgenstern-Price. A multiple repeated slope stability analysis took place in order to determinate the proper geometry (inclinations) of the slope with new benches. From the analysis of the data, the landslide restoration can be achieved with the combination of measures such as new benches geometry (proposed), surface drainage systems, retaining walls, soil nailing, geogrids and grass mat.